Ontario, Flint's travel companions in front of Hudson Bay Company trading post - Flint, Alfred T. (1933)
Hudson Bay Company Trading Post Manager, Mr. Taylor, standing in door with Flint's travel companions waiting on porch with gear. Grayscale Nitrate Negatives, Box 1